Workshop pembuatan soal fisika yang berorientasi kepada kemampuan berpikir tingkat tinggi - Kaharuddin Arafah; Herman Herman; A.J. Patandean (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
This activity aims to provide reinforcement to physics teachers who are members of the Subject Teacher (MGMP) IPA of Parepare City. In particular, the objectives of this program are: formulating the problem making grid, constructing item items, analyzing item items, calculating the validity and reliability of the assessment instruments of physics learning outcomes to measure higher-order thinking skills. To achieve this goal, a workshop was held for Physics teachers who are members of the MGMP IPA Parepare City. This workshop was held at SMAN 5 Parepare for 4 weeks. The first week was reinforced in the form of presentations on the technique of making lattices, and grain formulation techniques. Then the participants were given the task of making a grid. The second week there was a discussion about the grid, then continued with the theory of the formulation of the items. After that, they were invited to present in groups. In the third week, there was a presentation by the service team about the item analysis technique followed by assigning tasks to participants. Last week there was a discussion about the items the participants had made to ensure that all items produced by the participants were included in the HOTS category. The results of this activity indicate that, over 87% of participants in the MGMP IPA of Parepare City are able to make items about Physics that are oriented towards higher-order Thinking skills.